The maximal metabolic steady state: redefining the 'gold standard'. Issue 10 (23rd May 2019) - Jones, Andrew M.; Burnley, Mark; Black, Matthew I.; Poole, David C.; Vanhatalo, Anni
Abstract: The maximal lactate steady state (MLSS) and the critical power (CP) are two widely used indices of the highest oxidative metabolic rate that can be sustained during continuous exercise and are often considered to be synonymous. However, while perhaps having similarities in principle, methodological differences in the assessment of these parameters typically result in MLSS occurring at a somewhat lower power output or running speed and exercise at CP being sustainable for no more than approximately 20–30 min. This has led to the view that CP overestimates the 'actual' maximal metabolic steady state and that MLSS should be considered the 'gold standard' metric for the evaluation of endurance exercise capacity. In this article we will present evidence consistent with the contrary conclusion: i.e., that (1) as presently defined, MLSS naturally underestimates the actual maximal metabolic steady state; and (2) CP alone represents the boundary between discrete exercise intensity domains within which the dynamic cardiorespiratory and muscle metabolic responses to exercise differ profoundly. While both MLSS and CP may have relevance for athletic training and performance, we urge that the distinction between the two concepts/metrics be better appreciated and that comparisons between MLSS and CP, undertaken in the mistaken belief that they are theoretically synonymous, is discontinued. CP represents the genuine boundary separating exercise in which physiological homeostasis can be maintained from exercise in which it cannot, and should be considered the gold standard when the goal is to determine the maximal metabolic steady state. Abstract : The maximal lactate steady state (MLSS) and the critical power (CP) are two indices of the highest oxidative metabolic rate that can be sustained during continuous exercise and are often considered to be synonymous. We discuss evidence consistent with the interpretation that CP provides a more robust representation of the boundary separating exercise domains wherein a metabolic steady‐state can or cannot be achieved.